2017
DOI: 10.1177/1941874417729982
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Pharmacist Impact on Door-to-Needle Time in Patients With Acute Ischemic Stroke

Abstract: The EMP involvement in initial stroke care was associated with a significant improvement in DTN time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 14 publications
4
27
0
Order By: Relevance
“…Expedited administration of rTPA for AIS remains an ongoing quality improvement initiative for many stroke centers across the country. The utilization of pharmacists in stroke teams has been shown to improve overall DTN administration times, but this is one of the first studies to examine the impact pharmacist have on the guideline specific recommendation of a DTN administration time of less than 60 minutes . Reduction in overall administration times can prove controversial given that the “time is brain” concept is not universally endorsed in the medical community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expedited administration of rTPA for AIS remains an ongoing quality improvement initiative for many stroke centers across the country. The utilization of pharmacists in stroke teams has been shown to improve overall DTN administration times, but this is one of the first studies to examine the impact pharmacist have on the guideline specific recommendation of a DTN administration time of less than 60 minutes . Reduction in overall administration times can prove controversial given that the “time is brain” concept is not universally endorsed in the medical community.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature have shown some of the beneficial impact that including an ED pharmacist into the stroke team can provide . Most of the literature with regard to pharmacist involvement in AIS have been with a reduction in DTN administration times and more accurate dosing of rTPA, without focusing on the overall goal metric of a DTN administration time of 60 minutes or less . Debate will continue as to whether faster administration of rTPA leads to better functional outcomes, but for now, the standard for stroke centers is rapid rTPA administration based on the AHA guideline of a DTN administration time of 60 minutes or less .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort of patients receiving tissue plasminogen activator (tPA) for acute ischemic stroke found a pharmacist's presence at the bedside decreased median door‐to‐needle time by 23.5 minutes . This finding was confirmed by other studies as well . Although no data currently quantify the CA associated with having a pharmacist on the stroke team, a cost‐economic analysis found that delivery of tPA within 3–4.5 hours was associated with $1495 saved per patient compared with no tPA .…”
Section: Results Of Scoping Reviewmentioning
confidence: 82%
“…63 This finding was confirmed by other studies as well. 64,65 Although no data currently quantify the CA associated with having a pharmacist on the stroke team, a cost-economic analysis found that delivery of tPA within 3-4.5 hours was associated with $1495 saved per patient compared with no tPA. 65 Taking into account that pharmacist involvement in stroke care increased the proportion of patients meeting the door-toneedle goal by 42%, CA is estimated at $627.90 per patient.…”
Section: Emergency Code Stroke Participation (Loe Iii)mentioning
confidence: 99%
“…Improve the people's understanding of the necessity of thrombolysis, time urgency and safety, and fully understand that the benefits of early thrombolysis far outweigh the risks [52,53]. Secondly, at the hospital level, 1) popularize the knowledge of cerebral infarction, improve the awareness of early thrombolytic therapy for patients and medical staff; 2) establish a referral mechanism for network hospitals; 3) open a green channel for thrombolytic therapy in patients with acute ischemic cerebral infarction; 4) train relevant professionals to improve clinical execution; 5) take a door-to-needle time (DNT) thrombolysis management system to shorten or eliminate in-hospital delay time and improve the response rate of thrombolytic therapy [54,55]. Third, in terms of doctors, 1) fully understand the importance of thrombolysis in AIS; 2) quickly identify patients with acute stroke, and grasp the emergency thrombolysis time window, indications and contraindications; 3) for patients with unknown onset time, IP can be determined by imaging; 4) be skilled in arterial thrombolysis and endovascular treatment and other related technologies, and can successfully complete bridging treatment; 5) can have the ability to cope with hemor-rhagic transformation after thrombolysis.…”
Section: Before Thrombolysismentioning
confidence: 99%